2000
DOI: 10.1177/0022022100031002007
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of the Five-Factor Model of Personality to Job Performance for a Group of Middle Eastern Expatriate Managers

Abstract: Studies in the United States and Europe have investigated the relationship of the Five- Factor Model of personality to effectiveness for domestic managers. This article reports on the relationship of the Five-Factor Model of personality to job performance for a group of Middle Eastern expatriate managers. Job performance ratings from the expatriate’s host- and home-country bosses indicate that agreeableness and conscientiousness were related to home-country ratings of job performance, but not host-country rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 12 publications
1
59
0
2
Order By: Relevance
“…Job performance is a multidimensional construct consisting of task dimension and contextual dimension (Borman & Motowidlo, 1993). A review of literature indicated individual differences such as gender (Caligiuri & Tung, 1999;Sinangil & Ones, 2003), Big Five Personality (e.g., Dalton & Wilson, 2000;Caligiuri, 2000;Mol et al, 2005), self-monitoring personality (Caligiuri & Day, 2000), goal orientation (Wang & Takeuchi, 2007), task and people orientation (Shaffer et al, 2006), cultural flexibility (Shaffer et al, 2006), non-ethnocentrism (Hechanova et al, 2003), communicational ability, relational ability, stress tolerance (Holopainen & Bjorkman, 2005), and previous international experience (Varma, Toh, & Budhwar, 2006) related to expatriate job performance.…”
Section: Employee Performancementioning
confidence: 99%
“…Job performance is a multidimensional construct consisting of task dimension and contextual dimension (Borman & Motowidlo, 1993). A review of literature indicated individual differences such as gender (Caligiuri & Tung, 1999;Sinangil & Ones, 2003), Big Five Personality (e.g., Dalton & Wilson, 2000;Caligiuri, 2000;Mol et al, 2005), self-monitoring personality (Caligiuri & Day, 2000), goal orientation (Wang & Takeuchi, 2007), task and people orientation (Shaffer et al, 2006), cultural flexibility (Shaffer et al, 2006), non-ethnocentrism (Hechanova et al, 2003), communicational ability, relational ability, stress tolerance (Holopainen & Bjorkman, 2005), and previous international experience (Varma, Toh, & Budhwar, 2006) related to expatriate job performance.…”
Section: Employee Performancementioning
confidence: 99%
“…Neurotic individuals tend to have relatively negative core self-evaluations, leading to emotional distress and associated behaviors (Rusting & Larsen, 1998). Neuroticism also related to a person's general tendency to experience negative effects such as fear, sadness, embarrassment, anger, guilt, and disgust (Dalton & Wilson, 2000). Albeit limited, the available studies have linked personality factor with various expatriate outcomes such CCA (Shaffer et al, 2006), job performance (Mol, Born, Willemsen & Van Der Molen, 2005) and premature return from assignment (e.g., Caligiuri, 2000a).…”
Section: Personalitymentioning
confidence: 99%
“…b. ns reflect subsets of the original sample in cases where criterion data were only available for that subset. Bolino & Feldman (2000) [ [ Caligiuri (2000) [ Caligiuri & Tung (1999) [ Dalton & Wilson (2000) [ Deller (2000) [ Feldman & Thomas (1992) [ ( ) Grösch (2004 [ Gross (2002) [ Guthrie & Zektick (1967) [ Harrison & Shaffer (2001) [ Kraimer et al (2001) [ Leslie, Dalton, Ernst, & [ [ [ [ [ Deal (2002) Liu (2003 [ Mischel (1965) [ Parker & McEvoy (1993) ( ) Schneider (1997 [ [ [ [ [ [ [ [ [ [ [ [ [ [ [ [ [ [ Shaffer et al (2003): Shaffer et al (2003): Study 2 Shaffer et al (2003): …”
Section: Categorizationmentioning
confidence: 99%
“…In this respect, Arthur and Bennett (1995) note that more than five decades of research on expatriate selection has failed to yield a clear and explicit knowledge structure of what it is we should be training and selecting for. Evidence for different schools of thought may be found in the fact that some researchers seek an answer to this criterion issue in the expatriate's adjustment (e.g., Black, 1990), whereas others (e.g., Dalton & Wilson, 2000) emphasize the expatriate's job performance as the criterion of choice.Although the antecedents and consequences of expatriate adjustment have been well documented (see Bhaskar-Shrinivas, Harrison, Shaffer, & Luk, 2005;Hechanova, Beehr, & Christiansen, 2003, for meta-analytic reviews), many authors within the expatriate management literature have lamented the unavailability of job performance criteria for expatriates (see, e.g., Arthur & Bennett, 1995Hawes & Kealey, 1979;Kealey & Protheroe, 1996;Mol, Born, & Van der Molen, 2003;Ones & Viswesvaran, 1997;Sinangil & Ones, 2001;Werner, 2002).Nevertheless, there has recently been an increase in empirical publications vis-à-vis expatriate job performance. This is affirmed by two meta-analytic publications about the relationship between training and expatriate job performance (see Deshpande & Viswesvaran, 1992;Morris & Robie, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation